Translation of polyoma virus T antigens in vitro. - Hunter, T (1978)
Polyoma virus-specific RNA isolated from the cytoplasm of lytically infected cells can be translated in vitro to yield three T antigens, of Mrs approximately 90,000, 60,000, and 22,000. The tryptic peptide patterns of the T antigens synthesized in vitro are similar or identical to the patterns of the corresponding proteins in polyoma-infected cells. All three proteins incorporate methionine donated from initiator tRNA in vitro. Polyoma cRNA codes for a protein that is slightly larger than the 22,000 T antigen and that, by other criteria, is similar to the 22,000 T antigen. Translation of cRNA does not yield the 90,000 and 60,000 T antigens, suggesting that the generation of the mRNAs for these T antigens requires the removal of intervening sequences. The mRNA for the 90,000 T antigen is smaller than the mRNAs for the 22,000 and 60,000 proteins. All three proteins share common NH2-terminal sequences, and the 60,000 T antigen may be translated partially in a different reading frame from sequences also coding for the 90,000 T antigen. The demonstration that polyoma virus codes for three different T antigens raises the possibility that all three proteins may be involved in cell transformation.